A review of the biopsychosocial aspects of caregiving for aging family members. Issue 5 (19th October 2016) - Colvin, Alex D.; Bullock, Angela N.
ABSTRACT: With the ever-increasing growth in the aging population, the need for care providers will also continue to rise. Many of these caregivers will provide informal care to family members and friends at a price to their own physical, psychological, and social well-being. This article examines the phenomenon of caregiving and provides a review of the biological, psychological, and social impacts of caregiving to care providers. George Engel's biopsychosocial model is explored to examine the biological, psychological, and social factors that can affect a caregiver's health and well-being. This article further explores social work practice implications and strategies for future intervention to reduce caregiver burnout and aid in their self-preservation.